Health sector reform in the Republic of Trinidad and Tobago - Rafeeq, Hamza (2000)
Highlights the challenges that the regional health authorities (RHA) have faced viz. governance; transfer of public service staff to the RHAs; continued provision of national public health services; coherence in the delivery of care throughtout the country; and, financing of the health sector.